2019
DOI: 10.33140/jepr.01.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Wellbeing in Schools: A New Framework to Guide the Science of Positive Education

Abstract: Youth mental illness has reached alarming rates globally and, as such, international organizations such as the United Nations and the World Health Organization are calling for schools to play an active role in preventing youth distress and promoting youth wellbeing. With this in mind, the field of positive education, now a decade old, has much to offer with its emphasis on bringing the science of positive psychology to schools. However, the rapid growth of positive education has created a potentially fragmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Results from this study found that wellbeing literacy in students grew significantly after their teachers had undertaken a positive education intervention. Teachers were trained in the science and practice of wellbeing using the SEARCH framework (Waters, 2019;Waters & Loton, 2019) and were shown how to implement positive education language and practices in the classroom. When this occurred, post-intervention student literacy evolved in four key ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study found that wellbeing literacy in students grew significantly after their teachers had undertaken a positive education intervention. Teachers were trained in the science and practice of wellbeing using the SEARCH framework (Waters, 2019;Waters & Loton, 2019) and were shown how to implement positive education language and practices in the classroom. When this occurred, post-intervention student literacy evolved in four key ways.…”
Section: Discussionmentioning
confidence: 99%
“…Visible Wellbeing trains teachers in a language, framework and practices for seeing and building the wellbeing of their students. The evidence-based framework that underpins the VWB intervention is called SEARCH (Waters, 2019;Waters & Loton, 2019). The SEARCH framework covers six overarching pathways to wellbeing: strengths, emotional management, attention and awareness, relationships, coping and habits, and goals.…”
Section: Methodsmentioning
confidence: 99%
“…The current case study adopted the SEARCH positive education framework (Waters, 2017b(Waters, , 2019(Waters, , 2021Waters & Loton, 2019). SEARCH is a framework that comprises six pathways to well-being: strengths, emotional management, attention and awareness, relationships, coping, and habits and goals.…”
Section: Search: a Positive Education Frameworkmentioning
confidence: 99%